2006
DOI: 10.1016/j.acn.2005.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decline in Digit–Symbol performance: Eye-movement and video analysis

Abstract: Examines age-related decline in Digit-Symbol performance using variables obtained from a slow-motion analysis of a first person perspective video filmed during test completion, including superimposed cross-hairs indicating eye movements. Standard WAIS-3 DSCT scores and the video-derived variables were compared across two age groups (mean age 20 years vs. mean age 59 years). The older group performed more poorly overall, t(16)=-2.359, p=.031. The correlation between writing time per item and overall performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…Joy et al44,45 suggest, with experimental support, that digit symbol performance in young healthy subjects is comprised of independent contributions from motor speed, cognitive speed, and visual scanning efficiency primarily and, to a lesser extent, from visual memory (for digit-symbol pairs) and set-shifting ability (between digits and symbols). Two further studies,46,47 also in young healthy subjects, analyzed eye movements during digit symbol performance and found that time spent inspecting the code correlated highly with performance whereas time spent writing did not. This suggests that the speed of searching and encoding information was a more important process than simple motor speed for performance.…”
Section: Discussionmentioning
confidence: 99%
“…Joy et al44,45 suggest, with experimental support, that digit symbol performance in young healthy subjects is comprised of independent contributions from motor speed, cognitive speed, and visual scanning efficiency primarily and, to a lesser extent, from visual memory (for digit-symbol pairs) and set-shifting ability (between digits and symbols). Two further studies,46,47 also in young healthy subjects, analyzed eye movements during digit symbol performance and found that time spent inspecting the code correlated highly with performance whereas time spent writing did not. This suggests that the speed of searching and encoding information was a more important process than simple motor speed for performance.…”
Section: Discussionmentioning
confidence: 99%
“…The dual-task cost score was calculated as follows: ((single-task score−dual-task score)/single-task score)×100. All cost scores were converted to age-corrected Z -scores based on the performance of the normal control group (Stephens, 2006; Sullivan et al , 2000b) and used in all subsequent analyses to remove the effect of normal age.…”
Section: Methodsmentioning
confidence: 99%
“…The DSST is a subtest of the WAIS-Revised [44]. Test scores correlate with general intelligence, cognitive impairment, chronological age, and activation in the frontal regions [4749]. Participants are presented with a rectangular grid of numbers.…”
Section: Outcome Variablesmentioning
confidence: 99%